147. Clinical Safety and Efficacy of Novel Antifungal, Fosmanogepix, in the Treatment of Candidemia: Results from a Phase 2 Proof of Concept Trial. (31st December 2020) - Pappas, Peter; Kullberg, Bart Jan; Vazquez, Jose A; Oren, Ilana; Rahav, Galia; Aoun, Mickaël; Bulpa, Pierre; Ben-Ami, Ronen; Ferrer, Ricard; McCarty, Todd P; Thompson III, George R; Barbat, Sara; et al.
Abstract: Background: Fosmanogepix (FMGX) is a first-in-class antifungal agent, with a unique MOA targeting the fungal enzyme Gwt1, that has broad-spectrum activity against both yeasts, molds, and dimorphic fungi, including fungi resistant to other antifungal agents. FMGX has a favorable safety profile, reduced potential for clinically significant drug-drug interactions, and is formulated for IV and oral administration. Methods: This global, multicenter, open-label, non-comparative study evaluated the safety and efficacy of FMGX for first-line treatment of candidemia. Patients with a recent diagnosis of candidemia defined as positive blood culture for Candida spp. within 96 hrs prior to study entry, with ≤2 days of prior antifungal treatment were eligible. Patients with neutropenia, C. krusei infection, or deep-seated Candida infections were excluded. Patients were treated with FMGX for up to 14 days: 1000 mg IV BID for 1 day, then 600 mg IV QD for at least 2 days, followed by either 600 mg IV QD or 700 mg PO QD. Short-term fluconazole (or appropriate alternative) could follow if treatment was required beyond 14 days. Patients with a diagnosis of candidemia within 96 hrs of start of study drug who received at least 1 dose of FMGX were included in the mITT population. The primary efficacy endpoint was outcome at end of study treatment (EOST) as determined by an independent data review committee (DRC). Successful outcome was defined as clearance of Candida from blood cultures with no additional antifungal treatment and survival at EOST. All Candida isolates were tested for antifungal susceptibility. Results: A total of 21 subjects were enrolled in the study: 20 were included in the mITT. Median duration of FMGX was 11 days (range 5–14). All subjects received IV FMGX, 48% (10/21) received PO FMGX. The DRC-assessed success rate at EOST was 80% (16/20). Survival at day 30 was 85% (17/20); 3 deaths were not related FMGX. FMGX was well-tolerated with no treatment-related serious adverse events or discontinuations. FMGX had potent in vitro activity against all study Candida spp. (EUCAST MIC range 0.001–0.03 µg/ml) including those resistant to other antifungal agents. Conclusion: FMGX was safe, well-tolerated, and demonstrated proof of concept with a high level of treatment success in patients with candidemia. Disclosures: Peter Pappas, MD, SCYNEXIS, Inc. (Consultant, Advisor or Review Panel member, Research Grant or Support) Bart Jan Kullberg, MD, FRCP, FIDSA, Amplyx (Advisor or Review Panel member) Galia Rahav, MD, AstraZeneca (Scientific Research Study Investigator) Mickaël Aoun, MD, Amplyx Pharmaceuticals (Scientific Research Study Investigator) Pierre Bulpa, MD, Amplyx Pharmaceuticals (Scientific Research Study Investigator) Ricard Ferrer, MD, PhD, Shionogi B.V. (Advisor or Review Panel member) Todd P. McCarty, MD, Amplyx (Scientific Research Study Investigator)Cidara (Scientific Research Study Investigator) Sara Barbat, BSN, RN, Amplyx Pharmaceuticals (Employee) Pamela Wedel, BSc, Amplyx Pharmaceuticals (Employee) Iwonka Oborska, PhD, Amplyx Pharmaceuticals (Consultant, Independent Contractor) Haran T. Schlamm, MD, Amplyx (Consultant) Michael Hodges, BSc. MD, Amplyx Pharmaceuticals Inc. (Employee)